De Novo Malignancies after Liver Transplantation: A Multicenter Cohort Study of Incidence, Timing, and Outcomes* - Danış, Nilay; Döngelli, Hüseyin; Ünek, Tarkan; Bacakoğlu, Aylin; Turan, İlker and Karasu, Abdullah Zeki and Günşar, Fulya and Işık, Elvan and Harputluoglu, Muhsin Murat and Sağlam, Kutay and et al. (Turkish Journal of Gastroenterology, 2026)
Background/Aims: De novo malignancies are an important long-term complication following liver transplantation (LT), driven by chronic immunosuppression and extended post-transplant survival. Understanding patterns by tumor type, timing, and patient characteristics is essential for optimized surveillance. This study aimed to evaluate the clinical characteristics and temporal trends of de novo neoplasms in LT recipients. Materials and Methods: A total of 6943 adult LT recipients from 16 Turkish centers were evaluated between 1999 and 2023). Two hundred eight patients with 220 histologically confirmed de novo malignancies (excluding hepatocellular carcinoma) were included. Patients who died within 30 days or developed cancer within 90 days post-LT were excluded. Incidence and mortality rates were assessed across post-transplant intervals. Results: Non-skin solid (53.2%), dermatologic (28.6%), and hematologic (18.2%) cancers were predominant. Most malignancies (76.8%) occurred within 10 years post-LT. Early-onset (<10 years) malignancies were more common in living donor recipients (62.7%, P = .001) and associated with higher mortality (39.6% vs. 11.8%, P < .001). Recipients ≤60 years exhibited a higher incidence of hematologic cancers (23.9% vs. 12.6%, P = .03) and increased mortality (39.4% vs. 27.0%, P = .05). In subgroup analysis, tacrolimus use was strongly associated with cutaneous squamous cell carcinoma (P = .004). Peak incidence occurred 2-10 years post-LT (≈13-14 per 1000 recipients), with non-skin solid tumors being the most frequent. Conclusion: De novo malignancies remain a significant long-term risk after LT, with outcomes influenced by tumor type, age, immunosuppression, and timing of onset. Risk-adapted surveillance and tailored oncologic management, particularly dermatologic screening in tacrolimus-treated patients and enhanced surveillance during the 2-10 year post-transplant period are recommended to improve long-term survival. Cite this article as: Danış N, Döngelli H, Ünek T, et al. De novo malignancies after liver transplantation: A multicenter cohort study of incidence, timing, and outcomes. Turk J Gastroenterol. Published online February 20, 2026. doi:10.5152/tjg.2026.25748.